Exploratory cohort study into underlying mechanism of differences in estrogen metabolism between Asian and Caucasian women during assisted reproductive technology treatment - Amy Kaing, M.D; Amanda Adeleye, M.D; Bani Tamraz, Pharm.D., Ph.D; Victor Y. Fujimoto, M.D (Elsevier, 2023)
Objective: Explore whether racial differences in prevalence of CYP1A2∗1F polymorphism underlies estrogen metabolism differences among Asians and Caucasians. Design: Prospective cohort study. Setting: University-based fertility practice. Patient(s): Asian or Caucasian patients who underwent ovarian stimulation (OS) or programmed cycle frozen embryo transfer (FET) between October 2019 and April 2021. Intervention(s): None. Main Outcome Measure(s): Trigger-day serum E2 per oocyte retrieved in OS cycles, and E2 on day of lining check in FET cycles. Result(s): Seventy-one participants were enrolled, 55 in OS group (29 Caucasian and 26 Asian) and 16 in FET group (10 Caucasian and 6 Asian). Peak E2 per oocyte retrieved in the OS group (n = 48) differed by race, with significantly lower levels in Caucasians compared with Asians (177.5 ± 64.2 vs. 261.1 ± 139.5 pg/mL). Prevalence of CYP1A2∗1F polymorphism did not significantly differ by race. Compared using Kruskal-Wallis test, peak E2 per oocyte retrieved did not differ by CYP1A2∗1F genotype. In multivariate linear regression model, adjusting for body mass index, caffeine intake, and self-reported race, there remained no significant correlation. In FET group, serum E2 on day of lining check was also not significantly different by CYP1A2∗1F genotype. Conclusion(s): Although a consistent difference in serum E2 between Asians and Caucasians undergoing OS was noted, the CYP1A2∗1F polymorphism is unlikely the primary driver of this difference.